2015
DOI: 10.1021/acs.jpca.5b07308
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Study of the Memory Effect in Model Natural Gas Hydrate Systems

Abstract: A high pressure automated lag time apparatus (HP-ALTA) was used for the investigation of the controversial memory effect in methane-propane mixed gas hydrates. The instrument can apply a large number of linear cooling ramps to a small volume of sample water under an isobaric condition of up to 15 MPa and record the maximum achievable subcooling for each cooling ramp. Over a hundred nucleation events were recorded for each of the several superheating temperatures used for the dissociation of the gas hydrate in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 36 publications
2
40
1
Order By: Relevance
“…These early observations appear to have been forgotten, but in more recent times memory effects have been observed quite regularly as discussed by Sloan [50], who also promoted the residual structure hypothesis discussed below. Many other researchers have contributed results and suggestions for mechanisms as recently reported by Sowa and Maeda [51]. We think that one can safely conclude that the memory phenomenon has been well documented and supported by many trained observers over a period of more than 100 years.…”
Section: Hydrate Decomposition and Memory Effectssupporting
confidence: 68%
See 1 more Smart Citation
“…These early observations appear to have been forgotten, but in more recent times memory effects have been observed quite regularly as discussed by Sloan [50], who also promoted the residual structure hypothesis discussed below. Many other researchers have contributed results and suggestions for mechanisms as recently reported by Sowa and Maeda [51]. We think that one can safely conclude that the memory phenomenon has been well documented and supported by many trained observers over a period of more than 100 years.…”
Section: Hydrate Decomposition and Memory Effectssupporting
confidence: 68%
“…In 2015, Sowa and Maeda offered ''Even though the nucleation phenomena were intrinsically stochastic, a clear bias was observed which supported the existence of the memory effect" [51]. This suggests very modest progress in explaining the memory phenomenon, however, they did suggest three leading candidates for explaining the memory effect, and categorized, the by now better defined, deterministic variables suggested by Parent and Bishnoi [54].…”
Section: Hydrate Decomposition and Memory Effectsmentioning
confidence: 98%
“…The sample was then heated just above hydrate-liquid-vapor equilibrium temperature, at the experimental pressure, to dissociate the initial hydrate [25]. Discussion on crystal formation history is beyond the scope of this paper, but interested readers are referred to the literature on this topic as applied to gas hydrates [27][28][29][30].…”
Section: Crystal Formation Historymentioning
confidence: 99%
“…Two major reasons have been proposed to explain this phenomenon [30,38,45,[48][49][50][51][52]. The first and oldest one is the presence of some sort of residual molecular structures in the aqueous phase that can persist for a long time after dissociation, being transformed in nucleation sites when cooled again.…”
Section: Hydrate Formationmentioning
confidence: 99%
“…Sowa and Maeda [48], in turn, used a high pressure automatic lag time apparatus (HP-ALTA) to test the memory effect in ethane-propane mixed gas hydrates by four different boats. They concluded that the memory effect do exist, but its amount varied among the boats.…”
Section: Hydrate Formationmentioning
confidence: 99%